Reversibility of High-Grade Atrioventricular Block with Revascularization in Coronary Artery Disease without Infarction: A Literature Review - Rhanderson Cardoso; Carlos E. Alfonso; James O. Coffey (Case Reports in Cardiology)
Complete atrioventricular (AV) block is known to be reversible in some cases of acute inferior wall myocardial infarction (MI). The reversibility of high-grade AV block in non-MI coronary artery disease (CAD), however, is rarely described in the literature. Herein we perform a literature review to assess what is known about the reversibility of high-grade AV block after right coronary artery revascularization in CAD patients who present without an acute MI. To illustrate this phenomenon we describe a case of 2 : 1 AV block associated with unstable angina, in which revascularization resulted in immediate and durable restoration of 1 : 1 AV conduction, thereby obviating the need for permanent pacemaker implantation. The literature review suggests two possible explanations: a vagally mediated response or a mechanism dependent on conduction system ischemia. Due to the limited understanding of AV block reversibility following revascularization in non-acute MI presentations, it remains difficult to reliably predict which patients presenting with high-grade AV block in the absence of MI may have the potential to avoid permanent pacemaker implantation via coronary revascularization. We thus offer this review as a potential starting point for the approach to such patients.